360 Sex Differences in Adipose Tissue Quantity and Distribution in Newborn Infants. (October 2012) - Logan, KM; Hyde, MJ; Gale, C; Parkinson, JR; Jeffries, S; Modi, N
Abstract : Background and Aims: Adipose tissue (AT) quantity and distribution influence metabolic health. In adult life women have greater total and subcutaneous AT, but men have greater internal abdominal AT ( Gender Medicine, 2009; 6: 60–75). We aimed to explore AT volume and distribution in newborn male and female infants using magnetic resonance imaging (MRI). Methods: A retrospective observational study was performed, using an existing database of neonatal body composition data, to compare male and female healthy term infants. Results: Conclusions: Female newborn infants have higher total and subcutaneous AT, but similar internal abdominal AT compared to males. Longitudinal study is required to assess gender specific alterations in AT distribution during infancy and childhood, and may identify possible influences of internal abdominal AT development in males.